Analysis of muscular activity in archery: A comparison of skill level - Shinohara, H.; Urabe, Y. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: A series of archery shooting movements requires strong activity of muscles attached to the shoulder girdle and upper extremity. It is unclear which muscles influence archery competition scores. This study aimed to compare muscle activity of the shoulder girdle and upper extremity during shooting movements and to analyze the muscles influencing in archery skill improvement. METHODS: Thirty male archers, who were divided into three groups based on skill level (elite, pre-elite, and beginner), were included in this study. The angle of shoulder joint abduction, horizontal extension, and elbow joint flexion, as well as the electromyographic activity of the upper trapezius, lower trapezius, deltoid middle, deltoid posterior, biceps brachii, and triceps brachii muscles at the point of stabilization during shooting, were measured. RESULTS: In the elite group, the activity of the lower trapezius muscle was significantly higher (P<0.05), while that of the biceps brachii and triceps brachii muscles were significantly lower (P<0.05) compared to the pre-elite and beginner groups. CONCLUSIONS: The lower trapezius muscle of the draw arm is actively involved in scapular fixation during shooting. Therefore, in order to improve the archery competition score, training focused on the lower trapezius muscle is necessary.